PROFITABILITY, LEVERAGE, SIZE OF COMPANY TOWARDS TAX AVOIDANCE - Kimsen Kimsen; Imas Kismanah; Siti Masitoh (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2018)
The purpose of this research is to know the influence of Return On Assets (ROA), Debt To Equity Ratio (DER), and Asset to Tax Avoidance (TA) partially and simultaneously in the sector of various Industri listed in Indonesia Stock Exchange (IDX). The research period used is five years from 2012 to 2016. The study population included all industry miscellaneous sectors listed in Indonesia Stock Exchange (IDX) period 2012 to 2016. Sampling technique used is purposive sampling technique. Based on the predetermined criteria, the sample size was 8 companies. The type of data used was secondary data obtained from the Indonesia Stock Exchange website. Data analysis method used was panel data regression analysis. The result of F-test and t-test showed return on assets had an effect on tax avoidance, while debt to equity ratio had a positive influence on tax avoidance.